Cyclotides Isolated from an Ipecac Root Extract Antagonize the Corticotropin Releasing Factor Type 1 Receptor - Fahradpour, Mohsen; Keov, Peter; Tognola, Carlotta; Perez-Santamarina, Estela; McCormick, Peter J.; Ghassempour, Alireza; Gruber, Christian W. (Frontiers in Pharmacology, 2017)
Cyclotides are plant derived, cystine-knot stabilized peptides characterized by their natural abundance, sequence variability and structural plasticity. They are abundantly expressed in Rubiaceae, Psychotrieae in particular. Previously the cyclotide kalata B7 was identified to modulate the human oxytocin and vasopressin G protein-coupled receptors (GPCRs), providing molecular validation of the plants’ uterotonic properties and further establishing cyclotides as valuable sources for novel GPCR ligand design. In this study we screened a cyclotide extract derived from the root powder of the South American medicinal plant ipecac (Carapichea ipecacuanha) for its GPCR modulating activity of the corticotropin-releasing factor type 1 receptor (CRF1R). We identified and characterized seven novel cyclotides. One cyclotide, caripe 8, isolated from the most active fraction, was further analyzed and found to antagonize the CRF1R. A nanomolar concentration of this cyclotide (260 nM) reduced CRF potency by ~4.5-fold. In contrast, caripe 8 did not inhibit forskolin-, or vasopressin-stimulated cAMP responses at the vasopressin V2 receptor, suggesting a CRF1R-specific mode-of-action. These results in conjunction with our previous findings establish cyclotides as modulators of both class A and class B GPCRs. Given the diversity of cyclotides, our data point to other cyclotide-GPCR interactions as potentially important sources of drug-like molecules.